2014
DOI: 10.2174/18715206113139990328
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Evaluation of Novel 1,2,3,4-Tetrahydroisoquinoline Derivatives as Potent Antiglioma Agents

Abstract: Glioblastoma Multiforme (GBM) continues to demand improved chemotherapeutic solutions. In order to discover novel chemotherapeutic agents for GBM, we identified novel tetrahydroisoquinoline (THI) analogs as antiglioma agents. The present study reports the design, synthesis and in vitro evaluation of new THI derivatives in four established human glioma cell lines (T98, U87, LN18 and A172). Our structure activity relationship (SAR) studies revealed that the important modification of the carbon linker between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…EDL-360 was prepared as previously described [ 5 ]. For in vitro screening, a freshly prepared 50 μM stock solution was prepared by dissolving EDL-360 in DMSO.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…EDL-360 was prepared as previously described [ 5 ]. For in vitro screening, a freshly prepared 50 μM stock solution was prepared by dissolving EDL-360 in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is an urgent need to find new therapeutic approaches to improve patient survival and outcome. We previously showed that tetrahydroisoquinoline (THIQ) derivatives possessed potent antiglioma activity [ 5 ]. Structure activity relationship studies showed that EDL-360 is the most potent THIQ derivative against glioma cell cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heliamine is found in some Mexican cacti (Backebergia militaris, Carnegiea gigantea, Pachycereus pecten-aboriginum, Pachycereus pringlei, Pachycereus weberi) (Strombö m & Bruhn, 1978a,b;Mata & McLaughlin, 1980;Pummangura et al, 1982;Menachery et al, 1986) and exhibits strong anticancer action as an inhibitor of rat sarcoma (Strombö m & Bruhn, 1978a,b). Some derivatives of tetrahydroisoquinoline possess anticancer (Patil et al, 2014), antidiabetic (Song et al, 2014), antidepressant (Możdżeń et al, 2014;Antkiewicz-Michaluk et al, 2014a,b;Wąsik et al, 2014) and anticonvulsant (Gitto et al, 2010) action and also have contractile activity against guinea pig's gastric smooth muscle preparations (Ivanov et al, 2011). In addition, heliamines substituted by hydroxyl or carboxyl groups were shown to be low-molecular-weight hydrogelators (Kang et al, 2011(Kang et al, , 2014Xu et al, 2012) which are useful in catalytical and biological applications (Tian et al, 2014;Dö ring et al, 2013;Xu, 2009;Estroff & Hamilton, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The IC 50 values ranged from approximately 3-10 μM, depending on the cancer cell line. Therefore, we were interested in investigating the anti-cancer activity of other THIQ analogs in a panel of human glioma cell lines [166].…”
Section: Tetrahydroisoquinoline Derivativesmentioning
confidence: 99%